2011
DOI: 10.1007/s12185-011-0888-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics-based optimal dose prediction of donor source-dependent response to mycophenolate mofetil in unrelated hematopoietic cell transplantation

Abstract: Mycophenolate mofetil (MMF) has been widely used for prophylaxis against graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation (allo-SCT). However, no clear advantage over methotrexate has been reported, other than reduced incidence of mucositis. We speculated that the wide inter-individual variation of plasma mycophenolic acid (MPA) levels veiled the benefits of MMF. Data from 36 unrelated allogeneic bone marrow (allo-BMT) and cord blood transplantation (CBT) were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Whether this difference is also seen in matched sibling and unrelated donor HCT remains to be seen, but suggests that higher MMF dosing may be beneficial. Previous studies have also demonstrated that there is inter-individual variation of plasma levels of mycophenolic acid (MPA), the active form of MMF, and that patients with lower concentration of MPA may have increased GVHD compared to higher levels [29][30][31][32]. While lower dosing may have contributed to the increased risk of severe GVHD, this further highlights the importance and lack of standard regarding the optimal dosing and length of MMF for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this difference is also seen in matched sibling and unrelated donor HCT remains to be seen, but suggests that higher MMF dosing may be beneficial. Previous studies have also demonstrated that there is inter-individual variation of plasma levels of mycophenolic acid (MPA), the active form of MMF, and that patients with lower concentration of MPA may have increased GVHD compared to higher levels [29][30][31][32]. While lower dosing may have contributed to the increased risk of severe GVHD, this further highlights the importance and lack of standard regarding the optimal dosing and length of MMF for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Wide interpatient variability has been reported in the plasma levels of mycophenolate (MPA), an active form of MMF, even after the same MMF exposure; however, few reports have performed therapeutic drug monitoring in CBT. 3 Therefore, we performed a prospective cohort study to (1) determine the correlation between MPA concentration and incidence of severe PES or acute GVHD (aGVHD) after CBT and (2) compare the incidence of these complications with the historical cohort using CNI alone for GVHD prophylaxis after CBT.…”
mentioning
confidence: 99%
“…Total MPA levels in the plasma were measured using the enzyme multiplied immunoassay technique (EMIT) 7 (C 0 , C 1 , C 2 and C 4 , respectively), and C 8 (which means the trough level of the next administration) was assumed to be equal to C 0 values based on results of our preliminary analysis (n = 12 both at the first and third weeks) and other studies. 3,8,9 Area under the curve (AUC) 0-8 h was determined using the linear trapezoidal method, and the AUC 0-24 h was calculated as 3 × AUC 0-8 h . This method is one of the standards in the setting of MMF administration three times a day (every 8 h), 3,8 because MPA concentrations reached to the peak within 2 h from administration, and decreased linearly after 4 h. 9 Patients whose AUC 0-24 h was below the lower quartile were categorized in 'the lower concentration group' at each time point (first and third week).…”
mentioning
confidence: 99%
“…Three retrospective studies [49][50][51] suggested the safety and efficacy of MMF together with Tac or CsA as GVHD prophylaxis. Wakahashi et al [51] reported that the blood concentration of MMF at 2 h after the start of infusion could be a surrogate marker of the area under the curve and helpful for predicting acute GVHD development.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…Three retrospective studies [49][50][51] suggested the safety and efficacy of MMF together with Tac or CsA as GVHD prophylaxis. Wakahashi et al [51] reported that the blood concentration of MMF at 2 h after the start of infusion could be a surrogate marker of the area under the curve and helpful for predicting acute GVHD development. Nationwide studies conducted by Iida et al [52,53] found 157 patients after related donor transplantation and 440 patients after unrelated donor transplantation who had received MMF as GVHD prophylaxis, suggesting that MMF is now widely used in Japan.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%